Amateur Working-Class Soccer - Diana Mendes Machado da Silva (Journal of Festive Studies)
The term “Futebol de Várzea” (Floodplain Soccer) has become synonymous with amateur working-class soccer in the city of São Paulo, Brazil. The multiple reasons for this connection relate to how soccer was appropriated by the city’s popular segments in various community “associations” of the várzeas (floodplains). The associative form grew historically from a combination of experiences of elite colleges, unions, and factory workers in England, and popular associativism was the basis for the organization of sport in such places as the suburbs of São Paulo. While tournaments and championships organized competitions in the context of European expansionism, community sports festivities and festivals introduced and incorporated soccer into the city’s suburban and várzea daily life. Thus, through immigrant associations for mutual aid, religious, and Black brotherhoods, among other institutions, Várzea Soccer figured as a kind of archive of non-hegemonic practices of playful, festive, and sports interaction with the (sub)urban space. These practices, which left deep marks, are still present in how sport is experienced in the country.